EVALUATION OF THE FUNCTION OF DPRD LEGISLATION IN THE PROCESS OF FORMING REGIONAL REGULATIONS IN THE CITY OF SUKABUMI - Jaelani, Ijan; Sampurna, Rizki Hegia; Hikmat, Asep (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The Regional People's Representative Council (DPRD) as an element of government is explained in Law Number 23 of 2014, which stipulates that the DPRD and Regional Government have maximum autonomy within the framework of the Unitary State of the Republic of Indonesia. Articles 149 and 150 states that the DPRD has three main functions: legislation, budget, and supervision. The legislative function includes the creation of Regional Regulations (Perda) through DPRD initiatives or proposals, which are then discussed and approved or rejected. Sukabumi City Propemperda has targets and work plans in drafting regional regulations to create regional regulations that are productive and beneficial for the progress of the city. However, of the expected 59 Propemperda targets, only 37 were successfully realized. Of the 37 Propemperda that were passed as regional regulations, only 2 of them came from DPRD initiatives. This research aims to evaluate the function of DPRD legislation in the process of forming regional regulations in the City of Sukabumi, using William N. Dunn's (2003) public policy evaluation theoretical framework, which includes effectiveness, efficiency, adequacy, alignment, responsiveness, and accuracy. The research method used is descriptive qualitative, with data collection techniques in the form of semi-structured interviews, observation, and documentation studies. Data analysis was carried out based on the Miles and Huberman approach. The research results show that there are still many targets that have not been achieved each year, and the implementation of regional regulations is not always by the expected goals. The advice given is the need for commitment from the council and local government to implement regional regulations optimally